Irritable bowel syndrome dietary modifications - what to forbid and what to recommend? - Kaczyńska, Agnieszka; Wieteska, Małgorzata; Stanicki, Paweł; Szarpak, Julita (Journal of Education, Health and Sport, 2020)
Irritable bowel syndrom is a gastrointestinal disorder, that affects about 10 % of worlds population. The etiology remains unclear, however studies show, that bad dietary habits may aggravate the symptoms. The most frequent signs of IBS are: abdominal pain, bloating, constipation, diarrhea and change in bowel habits. The aim of this study was to describe dietary modifications that can alleviate the symptoms and improve patients quality of life. The study material consisted of publications, that we’ve found on databases as PubMed, ResearchGate and Google Scholar. Patients find out, that certain food aggravate the symptoms. The most frequent triggering factors are: coffee, diary products, alcohol, spicy foods and lipids. Our review shows, there are some recommendations that help patients in their everyday diet change. For example drinking at least 3 cups of coffee per day can reduce bloating and diarrhea, while drinking more than 1,5 L of other fluids per day can alleviate symptoms as constipation. According to studies, following a IBS diet can minimize the signs. Moreover, recently developed „IBS food pyramid” is based on actual recommendations and knowledge a visual and user-friendly tool helping patients in everyday diet changes. Unfortunately, still there is insufficient evidence of studies about dietary approaches. Well designed and randomized control trials are needed to improve efficacy, safety and knowledge about dietary modifications.